Estação Armênia: exílio, fé e reconstrução de vida na capital paulista: um estudo de caso a comunidade protestante - Carvalhaes, Sueli Aparecida Cardozo (2012)
Within a macro project identification of religious plurality connected with the country's ethnic diversity, this research project analyzed the difficulties and peculiarities of the group of Armenian immigrants who settled in Brazil since 1920. In the midst of a new social and cultural reality haw these immigrants established the cooperative relationship in the new community. Religious identity is a critical factor to understanding the structural characteristics that led to the establishment and survival in the urban region of Sao Paulo. Our research focused on the Protestant side and how it uses the religious elements connected to form and maintain their ethnic identity recreated in Brazil.